A Composite Polyadenylation Signal with TATA Box Function - Paran, Nir (American Society for Microbiology, 2000)
A variant polyadenylation signal, which is conserved and employed by mammalian hepadnaviruses, has a sequence resembling that of the TATA box. We report here that this composite box manifests all the promoter characteristics. It binds effectively TATA-binding protein with TFIIB and TFIIA in a synergistic manner. This capacity, however, is lost when the box is converted to a canonical and simple poly(A) signal. Furthermore, we show that it has promoter activity and supports transcription of reporter genes preferentially in liver-derived cells, a characteristic behavior of the hepatitis B virus (HBV) promoters. In addition, we show that the HBV noncanonical poly(A) signal supports transcription initiation from the viral genome, suggesting that it is a genuine promoter, possibly of the polymerase/reverse transcriptase gene. Finally, we found that this deviant poly(A) signal is crucial for HBV replication since a viral mutant with a canonical poly(A) box is impaired in replication. Our data, therefore, raise the interesting and novel possibility that a composite poly(A) box might have a dual function. At the level of DNA it functions as a promoter to initiate transcription, whereas at the level of RNA it serves as a poly(A) signal to process RNA. An interesting outcome of this strategy of gene expression is that it provides a novel mechanism for the synthesis of an approximately genome length transcript.